BAIT-FISH AND TUNA CATCHES AT MINICOY ISLAND (LAKSHADWEEP) IN RELATION TO LUNAR CYCLE DURING 1983-84 SEASON - Mohan, Madan; Kunhikoya, K K (Indian Journal of Fisheries, 2011)
The catches of bait-fish and tuna in relation to moon phases during1983-84 pole-and-line tuna-fishing season is discussed. Bait-fish and tuna catchesfor the season as a whole were relatively high during new-moon phase and low'during the last quarter of the moon. Tuna catches per kg of bait fish were highduring the last quarter of moon and low during newmoon phase. Efforts in bothbait fishing and tuna fishing and catehes-per-unit-of-effort of bait fishes and tunawere highest during newmoon phase, then decreased gradually and was lowest inthe last quarters.